Efektivitas Pelaksanaan Online Single Submission (OSS) Untuk Pelayanan Perizinan di Mal Pelayanan Publik Pekanbaru Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 2018 - Syafriadi, Syafriadi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The Pekanbaru City Government implemented the Online Single Submission (OSS) application by opening a Public Service Mall (MPP) that can be accessed by the public. This aims to provide ease of service for business actors. The application of this online-based system is very effective in cutting the bureaucratic chain and eradicating corruption. Apart from that, it can also increase investment achievements during the COVID-19 pandemic. This study aims to determine the effectiveness of Online Single Submission (OSS) Implementation for Licensing Services at the Pekanbaru Public Service Mall based on Government Regulation 24 of 2018. This research method is empirical law or non-doctrinal research, namely studying and analyzing primary data juridically obtained from the respondents. The results showed that the respondents were very satisfied with the online-based licensing services at the Pekanbaru City Government MPP. It is recommended that the implementation of OSS be accompanied by regional regulations as ordered by Article 349 of Law Number 23 of 2014 concerning the Regional Government.